2009
DOI: 10.1097/prs.0b013e3181bf806c
|View full text |Cite
|
Sign up to set email alerts
|

Force-Induced Craniosynostosis in the Murine Sagittal Suture

Abstract: BACKGROUND-The etiology of non-syndromic craniosynostosis remains elusive. While compressive forces have been implicated in premature suture fusion, conclusive evidence of forceinduced craniosynostosis is lacking. The purpose of this study was to determine if cyclical loading of the murine calvarium could induce suture fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…metopic and sagittal). Recently, an in vitro model of force-induced sagittal craniosynostosis has corroborated the importance of intrauterine constraint in the initiation of midline craniosynostosis (Oppenheimer et al 2009). Advanced maternal age (35 years and older) and birth weight (> 4000 g) are additional environmental components of sagittal NSC (Boulet et al 2008).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…metopic and sagittal). Recently, an in vitro model of force-induced sagittal craniosynostosis has corroborated the importance of intrauterine constraint in the initiation of midline craniosynostosis (Oppenheimer et al 2009). Advanced maternal age (35 years and older) and birth weight (> 4000 g) are additional environmental components of sagittal NSC (Boulet et al 2008).…”
Section: Introductionmentioning
confidence: 93%
“…metopic and sagittal). Recently, an in vitro model of force‐induced sagittal craniosynostosis has corroborated the importance of intrauterine constraint in the initiation of midline craniosynostosis (Oppenheimer et al. 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Also, Oppenheimer et al . has demonstrated that cyclical forces led to premature fusion of sagittal sutures 25 but the effect of changes in the stiffness of the cranial suture tissues in bone formation has yet to be investigated. Since bone generation is mediated by signalling mechanisms that include stimuli from the surrounding environment, pathological changes in the physiology of the sutures of children with craniosynostosis may be associated with changes in the stimuli provided by the extracellular environment that impairs the functional capacity of cells within the sutures to sense and respond to these stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…These growth alterations appear to occur both by tension and compression (Sun et al, 2004;Herring, 2008). However, compression has also been suggested to cause cessation of growth at the calvarial sutures (Oppenheimer et al, 2009). Cartilage is much less relatively affected by muscle loads compared to sutures and periodontal ligaments (Bjork and Skieller, 1983), and in humans the masticatory muscle phenotype is associated with variations in the vertical growth of the face, but not with sagittal growth (Rowlerson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%